Commutators of Complex Symmetric Operators (Communications in Mathematical Research, 2025)
Let $C$ be a conjugation on a separable complex Hilbert space $\mathcal{H}.$ Anoperator $T$ on $\mathcal{H}$ is said to be $C$-symmetric if $CTC = T^∗,$ and $T$ is said to be $C$-skew symmetric if $CTC=−T^∗$. It is proved in this paper that each $C$-skew symmetric operator can be written as the sum of two commutators of $C$-symmetricoperators.
Keywords: Complex symmetric operators; commutators; skew symmetric operators.